Development and Initial Characterization of the First 18F-CXCR2-Targeting Radiotracer for PET Imaging of Neutrophils - Spatz, Philipp; Chen, Xinyu; Reichau, Kora; Huber, Max; Mühlig, Saskia; Matsusaka, Yohji; Schiedel, Matthias; Higuchi, Takahiro; Decker, Michael (Journal of Medicinal Chemistry, 2024)
The interleukin-8 receptor beta (CXCR2) is a highly promising target for molecular imaging of inflammation and inflammatory diseases. This is due to its almost exclusive expression on neutrophils. Modified fluorinated ligands were designed based on a squaramide template, with different modification sites and synthetic strategies explored. Promising candidates were then tested for affinity to CXCR2 in a NanoBRET competition assay, resulting in tracer candidate 16b. As direct 18F-labeling using established tosyl chemistry did not yield the expected radiotracer, an indirect labeling approach was developed. The radiotracer [18F]16b was obtained with a radiochemical yield of 15% using tert-butyl (S)-3-(tosyloxy)pyrrolidine carboxylate and a pentafluorophenol ester. The subsequent time-dependent uptake of [18F]16b in CXCR2-negative and CXCR2-overexpressing human embryonic kidney cells confirmed the radiotracer’s specificity. Further studies with human neutrophils revealed its diagnostic potential for functional imaging of neutrophils.
CRIS-Team Scopus Importer:2024-05-10